Potential of using cerium oxide nanoparticles for protecting healthy tissue during accelerated partial breast irradiation (APBI). Issue 4 (April 2016) - Ouyang, Zi; Mainali, Madan Kumar; Sinha, Neeharika; Strack, Guinevere; Altundal, Yucel; Hao, Yao; Winningham, Thomas Andrew; Sajo, Erno; Celli, Jonathan; Ngwa, Wilfred
Highlights: Cerium oxide nanoparticles (CONPs) can be used for selective normal tissue protection. New balloon applicator coated with CONPs is designed for APBI. Treatment improvement can be achieved with little additional cost. Abstract: The purpose of this study is to investigate the feasibility of using cerium oxide nanoparticles (CONPs) as radical scavengers during accelerated partial breast irradiation (APBI) to protect normal tissue. We hypothesize that CONPs can be slowly released from the routinely used APBI balloon applicators—via a degradable coating—and protect the normal tissue on the border of the lumpectomy cavity over the duration of APBI. To assess the feasibility of this approach, we analytically calculated the initial concentration of CONPs required to protect normal breast tissue from reactive oxygen species (ROS) and the time required for the particles to diffuse to various distances from the lumpectomy wall. Given that cerium has a high atomic number, we took into account the possible inadvertent dose enhancement that could occur due to the photoelectric interactions with radiotherapy photons. To protect against a typical MammoSite treatment fraction of 3.4 Gy, 5 ng·g −1 of CONPs is required to scavenge hydroxyl radicals and hydrogen peroxide. Using 2 nm sized NPs, with an initial concentration of 1 mg·g −1, we found that 2–10 days of diffusion is required to obtain desired concentrations of CONPs in regions 1–2 cm away from the lumpectomy wall. The resultant dose enhancement factor (DEF) is less than 1.01 under such conditions. Our results predict that CONPs can be employed for radioprotection during APBI using a new design in which balloon applicators are coated with the NPs for sustained/controlled in-situ release from within the lumpectomy cavity.